2020
DOI: 10.1039/d0fo00777c
|View full text |Cite
|
Sign up to set email alerts
|

The dietary flavonoid eupatilin attenuatesin vitrolipid peroxidation and targets lipid profile in cancer HeLa cells

Abstract: Eupatilin, a dietary flavonoid, is an antioxidant agent against membrane lipid oxidative damage and induces cytotoxicity, apoptosis and abnormal mitosis, affecting lipid profile and mitochondrial potential in cancer HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(87 citation statements)
references
References 50 publications
8
78
0
1
Order By: Relevance
“…Moreover, in gastric cancer cells, eupatilin induces apoptosis by regulating apoptotic proteins such as BAX and BCL2 and inducing mitochondrial depolarization [8]. Eupatilin also induces apoptosis by mediating mitochondrial membrane depolarization in cervical cancer cells [18]. Similarly, we found that eupatilin can regulate the expression of the mitochondrial proteins BAK, BCL-xL, and cytochrome c, which are involved in apoptotic processes in colon cancer cells, as well as in mitochondrial depolarization.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, in gastric cancer cells, eupatilin induces apoptosis by regulating apoptotic proteins such as BAX and BCL2 and inducing mitochondrial depolarization [8]. Eupatilin also induces apoptosis by mediating mitochondrial membrane depolarization in cervical cancer cells [18]. Similarly, we found that eupatilin can regulate the expression of the mitochondrial proteins BAK, BCL-xL, and cytochrome c, which are involved in apoptotic processes in colon cancer cells, as well as in mitochondrial depolarization.…”
Section: Discussionsupporting
confidence: 51%
“…Activation of SREBP-1 to synthesize lipids is thought to be required to maintain rapid proliferation of tumor cells [ 37 ]. It has been reported that lipogenesis also contributes to the resistance to cell death by altering membrane lipid composition and sensitive to lipid peroxidation [ 12 , 38 40 ]. In gefitinib-sensitive PC9 cells, gefitinib caused a decrease in lipogenesis and attenuated the expression of SREBP1, mSREBP1, FASN, and SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Apabila enzim tersebut dihambat, maka kadar kolesterol dapat menurun (Ekananda, 2015;Santosa, et al, 2020). Hasil ini sejalan dengan penelitian yang dilakukan oleh Rosa et al (2020) yang menyatakan bahwa pada tikus yang diberikan diet tinggi flavonoid, berupa beras merah, dapat menurunkan kadar kolesterol, LDL dan trigliserida serta peningkatan kadar HDL secara signifikan (Rosa, et al, 2020). Senyawa flavonoid akan berikatan dengan enzim HMG-KoA reduktase sehingga akan terbentuk asam mevalonat yang kemudian menyebabkan sintesis kolesterol terhenti (Zeka, et al, 2017).…”
Section: Pembahasanunclassified